2014
DOI: 10.1182/blood.v124.21.lba-1.lba-1
|View full text |Cite
|
Sign up to set email alerts
|

Factor XI Antisense Oligonucleotide for Prevention of Venous Thrombosis

Abstract: BACKGROUND: Patients undergoing total knee arthroplasty are at risk for postoperative venous thromboembolism (VTE). The pathogenesis of postoperative VTE is incompletely understood, but tissue factor exposed at the surgical site is thought to be the major driver through the extrinsic pathway of coagulation. Experimental data indicate that reducing factor XI (FXI), a key component of the intrinsic pathway, attenuates thrombosis without causing bleeding, but the role of FXI in postoperative VTE in humans is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
173
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(184 citation statements)
references
References 10 publications
6
173
0
5
Order By: Relevance
“…In whites, an association of a F11 genetic variant with VTE suggests a causal relation, but we did not observe this genetic relation in African‐Americans. Clinical trial evidence that inhibition of factor XI can prevent VTE further supports its role in VTE etiology .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In whites, an association of a F11 genetic variant with VTE suggests a causal relation, but we did not observe this genetic relation in African‐Americans. Clinical trial evidence that inhibition of factor XI can prevent VTE further supports its role in VTE etiology .…”
Section: Discussionmentioning
confidence: 87%
“…Another study reported that patients with severe factor XI deficiency have reduced incidence of VTE . Moreover, a clinical trial showed that inhibition of factor XI prevents postsurgical VTEs .…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, the TF‐mediated thrombin activity appears to be propagated by an amplification loop via the coagulation factor FXI in hypertension. That pathway was proposed earlier in coagulation research (Gailani and Broze Jr, ) and can be exploited therapeutically to perform safe thromboprophylaxis (Buller et al ., ). Blocking FXI synthesis prevented localized thrombin generation in platelets and lowered pro‐inflammatory platelet‐monocyte complexes, the vascular accumulation of myeloid cells, ROS formation in the vessel wall and ultimately dampened the blood pressure increase in models of hypertension (Kossmann et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Data from FXI‐deficient animal models indicate that FXI deficiency results in a relatively mild bleeding disorder. A recent study demonstrated that FXI contributes to postoperative thrombosis and that reducing FXI concentrations in patients undergoing total knee arthroplasty helped to prevent DVT and appeared to be safe, doing so without increasing bleeding. These findings support the concept that inhibition of FXI may serve as a safe, specific, novel therapeutic approach to thrombosis treatment and prevention.…”
Section: Discussionmentioning
confidence: 69%